2017
DOI: 10.21474/ijar01/5377
|View full text |Cite
|
Sign up to set email alerts
|

A New Design Titanium Miniplate Versus Conventional 4-Hole Titanium Miniplate for Management of Mandibular Angle Fractures: A Comparative Study.

Abstract: Orofacial trauma surgery is the foundation from which the speciality of maxillofacial surgery arose, and has significantly expanded and developed over the last 50 years [2].The mandible is the largest and strongest facial bone, by virtue of its position on the face and its prominence; it is commonly fractured when maxillofacial trauma has been sustained [3].The causes of fracture of the mandible are chiefly road traffic accidents, interpersonal violence, falls, sports injuries and industrial trauma [4]. Mandib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In 2017, Saikrishna Degela et al [ 32 ] performed a similar study on 20 patients. The study showed mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Saikrishna Degela et al [ 32 ] performed a similar study on 20 patients. The study showed mixed results.…”
Section: Discussionmentioning
confidence: 99%